Probing intercultural experiences among students at Malaysian universities: development of intercultural competence model - Dalib, Syarizan; Harun, Minah; Yusof, Norhafezah; Ahmad, Mohd Khairie
This study aims to consider intercultural competence in the Malaysian setting. Specifically, we examine how the local students reflect on intercultural competence in their everyday situations in the campus. Using a qualitative approach, we explore their experiences interacting with the international students and their perspective on intercultural competence. We collect data from focus group and in-depth interviews with selected undergraduate students from three universities in Northern Malaysia. The findings highlight several themes which include intercultural experience, attitude, knowledge, interlingual communication strategies and the effort to learn about others’ language and culture to achieve effective and appropriate communication. The themes lead to the interactive model of intercultural competence which demonstrates self and other awareness of their encounters.